Enrichment, Bioaccumulation and Health Risks of Trace Metals in Soils and Leafy Vegetables Grown on the Banks of the Ugandan Lifeline River, River Rwizi - Rutehenda, Deus R.; Adaku, Christopher; Omara, Timothy; Angiro, Christopher; Ntambi, Emmanuel (World, 2024)
Urban vegetable farming in wetlands and riverbanks are common features of Ugandan cities. However, urbanization has led to various anthropogenic activities that can lead to the pollution of water resources, enrichment of pollutants in soils and, consequently, pollutant bioaccumulation in edible tissues of plants cultivated on such soils. In this study, we report on the levels of six trace metals (TMTs) in 75 samples of leafy vegetables (Brassica oleracea L., Spinacia oleracea L., Amaranthus hybridus L., Cucurbita pepo L. and Solanum nigrum L.) and soils (n = 75) grown on the banks of River Rwizi, the second longest river in Uganda only after the Nile River. The concentrations of TMTs (Mn, Zn, Cd, Pb, Cr and Cu) in edible vegetable tissues and soils were quantified using flame atomic absorption spectrometry. The mean concentrations (in mg kg−1) of the TMTs in the soil samples were 205–373.84 (Mn), 12.72–65.04 (Zn), 0.26–0.42 (Cd), 3.36–16.80 (Pb), 5.96–25.06 (Cr) and 2.83–35.27 (Cu). In vegetable samples, the concentrations ranged from 43.25 to 110.00 (Mn), 1.08 to 1.83 (Cd), 41.06 to 71.20 (Zn), 4.31 to 6.16 (Pb), 0.65 to 0.81 (Cr) and 5.70 to 14.35 (Cu). With the exception of Mn and Cr, the rest of the TMTs were bioaccumulated in the edible vegetable tissues (bioconcentration factors = 1.03 to 10.71). Considering chronic daily intake through ingestion, dermal contact and inhalation of the TMTs in soils from the banks of River Rwizi, there are no potential non-cancer and carcinogenic health effects that could be experienced in both adults and children. Consumption of leafy vegetables could pose both non-cancer health risks (from ingestion of Zn, Pb, Cr, Mn and Cd) and cancer health risks (due to intake of Cd) in both children and adults. There is therefore a need to enforce regulations to mitigate the pollution of River Rwizi for a more sustainable economic development.
Keywords: Trace metals; Human health risks; Soil contamination; Life-line river; Road river; Cancer risk